A Review on Enhancing Cupriavidus necator Fermentation for Poly(3-hydroxybutyrate) (PHB) Production From Low-Cost Carbon Sources - Zhang, Le; Jiang, Zicheng; Tsui, To-Hung; Loh, Kai-Chee; Dai, Yanjun; Tong, Yen Wah (Frontiers in Bioengineering and Biotechnology, 2022)
In the context of a circular economy, bioplastic production using biodegradable materials such as poly(3-hydroxybutyrate) (PHB) has been proposed as a promising solution to fundamentally solve the disposal issue of plastic waste. PHB production techniques through fermentation of PHB-accumulating microbes like Cupriavidus necator have been revolutionized over the past several years with the development of new strategies such as metabolic engineering. This review comprehensively summarizes the latest PHB production technologies via Cupriavidus necator fermentation. The mechanism of the biosynthesis pathway for PHB production was firstly assessed. PHB production efficiencies of common carbon sources including food waste, lignocellulosic materials, glycerol, and carbon dioxide were then summarized and critically analyzed. The key findings in enhancing strategies for PHB production in recent years, including pre-treatment methods, nutrient limitation, feeding optimization strategies, and metabolism engineering strategies were summarized. Furthermore, technical challenges and future prospects of strategies for enhanced production efficiencies of PHB were also highlighted. Based on the overview of the current enhancing technologies, more pilot-scale and larger-scale tests are essential for future implementation of enhancing strategies in full-scale biogas plants. Critical analyses of various enhancing strategies would facilitate the establishment of more sustainable microbial fermentation systems for better waste management and greater efficiency of PHB production.